2015
DOI: 10.1371/journal.pone.0133960
|View full text |Cite
|
Sign up to set email alerts
|

Length-Based Assessment of Coral Reef Fish Populations in the Main and Northwestern Hawaiian Islands

Abstract: The coral reef fish community of Hawaii is composed of hundreds of species, supports a multimillion dollar fishing and tourism industry, and is of great cultural importance to the local population. However, a major stock assessment of Hawaiian coral reef fish populations has not yet been conducted. Here we used the robust indicator variable “average length in the exploited phase of the population ()”, estimated from size composition data from commercial fisheries trip reports and fishery-independent diver surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 33 publications
0
61
0
1
Order By: Relevance
“…Relative abundance ranked from low (light gray) to high (dark gray, and ordered from shallow water to mesophotic depths along hard-bottom substrate and unconsolidated sampling sites. *Indicate species with spawning potential ratios <30 (Nadon et al, 2015). (B) Proportional relative abundance of functional groups subjected to extractive fishing pressures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relative abundance ranked from low (light gray) to high (dark gray, and ordered from shallow water to mesophotic depths along hard-bottom substrate and unconsolidated sampling sites. *Indicate species with spawning potential ratios <30 (Nadon et al, 2015). (B) Proportional relative abundance of functional groups subjected to extractive fishing pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Higher mesophotic abundances of some groups, and changes in predator communities is a potential indicator of depth refugia (Thresher and Colin, 1986;Bejarano et al, 2014;Andradi-Brown et al, 2016;Lindfield et al, 2016), particularly for the fishery-depleted target species that were more abundant in mesophotic depths (e.g., A. virescens, Caranx ignobilis, Figures 8D, 10), or for redatory species with larger mesophotic body sizes (e.g., C. melampygus, Figure 9C). Given that assessments of MHI reef fish stock exploitation rates and annual catch assignments remain largely constrained to fishery-independent, open-circuit diver depths (i.e., <30 m) or fisheries-dependent, commercial catch/recreational survey data obtained from indeterminate depths (Nadon et al, 2015), the use of BRUVS serves as a promising, shallower compliment to the deep-water camera system (BotCam) utilized for Hawaiian bottom fish stock assessments (Merritt et al, 2011). Finally, additional research parsing depth refugia vs. ontogeny effects in structuring reef fish communities would be beneficial, as largersized mesophotic planktivores ( Figure 9B) could be attributed to ontogenic migrations (Andradi-Brown et al, 2016) and may be less prone to mesophotic predation in lower-complexity habitats that do not provide adequate shelter to more vulnerable size classes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, organized fishing interests heckled crowds and decision makers at public meetings, filed petitions to delay an administrative decision, and lobbied new legislators in an attempt to block approval of rules. Respondents frequently reported that organized interests opposed any rules changes despite documented resource depletion across the Hawaiian archipelago (Friedlander and DeMartini 2002;Kittinger et al 2011;Nadon et al 2015). To overcome strategic costs, community members raised public awareness, lobbied legislators, and encouraged citizens to support their proposals.…”
Section: Strategic Costsmentioning
confidence: 99%
“…Sophisticated tenure arrangements once managed resources for a highly populated and politically complex society in pre-contact times (Beamer and Duarte 2006;Kirch 2010;Beamer 2014;Gonschor and Beamer 2014;. Although marine resources are depleted well below historical levels (Friedlander et al 2014;Nadon et al 2015), fishing and gathering remain socially and culturally significant, while providing an important component of food security for many Hawai'i residents (Vaughan and Vitousek 2013;. Coral reef fisheries depletion in many areas can in part be attributed to a departure from local level, culturally rooted, and place-based regulations to ineffective centralized management.…”
Section: Introductionmentioning
confidence: 99%